Variability of response to early puberty induction demonstrated by transverse uterine diameter measurement and a novel method of 3D breast imaging. (22nd April 2022) - Burt, Elizabeth; Yasmin, Ephia; Davies, Melanie C; Creighton, Sarah; Brain, Caroline; Ruff, Clifford; Learner, Hazel Isabella; Williams, Louise; Cameron‐Pimblett, Antoinette; Talaulikar, Vikram; Conway, Gerard
Abstract: Objective: Induction of puberty with exogenous oestrogen results in considerable variability in final uterine and breast volumes. We set out to quantify the variability of these two outcome measures with a view to establishing monitoring methods that could be used to individualise treatment protocols. Design: A prospective observational study. Participants: Sixteen participants with pubertal delay and primary amenorrhoea, due to hypogonadism were recruited from paediatric gynaecology and endocrinology clinics at University College London Hospital. A standardised protocol of transdermal 17β oestradiol (17βE) was used (Evorel™), with a starting dose of 12.5 mcg increasing to 25 mcg (patch changed twice weekly) after 4 months. Follow up was every 2 months for a total of 8 months. Measurements: Uterine dimensions using ultrasound, oestradiol concentrations and breast development assessed by both Tanner staging and 3D photographic imaging. Results: After 8 months of treatment, the changes in oestradiol concentrations (0–174 pmol), uterine volume growth (4.4–16.4 ml) and breast volume (1.76–140.1 ml) varied greatly between individuals. Of uterine parameters, transverse uterine diameter was most closely associated with serum oestradiol levels at 8 months (beta standardised coefficient = 0.80, p = .001). Change in breast volume was associated with age of treatment initiation (beta standardised coefficient 0.55 p = .04). Conclusions: We demonstrate variation in response to exogenous oestrogen, emphasising the necessity for individualised dose titration. In the absence of sensitive oestradiol assays, uterine transverse measurements may be used as a surrogate marker of oestrogen sensitivity to guide early dose adjustment. 3D breast imaging may provide a quantitative assessment of breast development to complement Tanner breast staging.